2019
DOI: 10.36378/juatika.v1i1.41
|View full text |Cite
|
Sign up to set email alerts
|

Uji Beberapa Sifat Fisika Tanah Bekas Tambang Emas Tanpa Izin ( Peti ) Di Tiga Kecamatan Di Daratan Sepanjang Sungai Kuantan

Abstract: ABSTRAK   Penelitian ini berjudul Uji Beberapa Sifat Fisika Tanah Bekas Tambang Emas Tanpa Izin ( Peti ) di Tiga Kecamatan Di Daratan Sepanjang Sungai Kuantan. Waktu penelitian selama 5 bulan terhitung dari bulan Agustus sampai dengan Desember 2015. Tujuan penelitian ini adalah untuk mengetahui beberapa sifat fisika tanah bekas tambang emas tanpa izin (PETI) di tiga Kecamatan di daratan sepanjang bagian hilir sungai kuantan. Pelaksanaan penelitian ini dilakukan dengan menggunakan metode survai yang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…Soil specific gravity indicates the overall level of density of solid soil particles filling the pore space per soil layer. The value of soil specific gravity at the research site also increased significantly from layer (0-10 cm) to layer (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and (26-50) with a value of 2.10 g/cm-3, 2.14 g/cm-3, and 2.82 g/cm-3. This indicates that the deeper the soil layer, the higher the mineral content of the soil.…”
Section: Soil Type Weightmentioning
confidence: 86%
See 1 more Smart Citation
“…Soil specific gravity indicates the overall level of density of solid soil particles filling the pore space per soil layer. The value of soil specific gravity at the research site also increased significantly from layer (0-10 cm) to layer (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and (26-50) with a value of 2.10 g/cm-3, 2.14 g/cm-3, and 2.82 g/cm-3. This indicates that the deeper the soil layer, the higher the mineral content of the soil.…”
Section: Soil Type Weightmentioning
confidence: 86%
“…In addition, crate activities generally do not follow proper sops (operational standards of implementation) in exploring, processing and managing tailings waste, causing negative impacts on the environment and living things (Qishlaqi & Moore, 2007).PETI activities are increasingly massive effect on the decline in soil fertility and aesthetic value of the environment. Several studies have reported that the condition of the former mining soil causes the dominant soil texture of sand, damaged soil structure, organic matter and nutrient levels tend to be low-very low and the ability to retain nutrients and low water (Henrianto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The sorption of Hg by soil involves the interaction between Hg ions with soil colloids, clays, and soil organic matter. Exgold mining soils are dominated by the sand fraction (>70%) (Henrianto et al, 2019). The clay fraction of the ex-gold mining soil amounted to 7.23%.…”
Section: Application Of Sub-bituminous Coal On Ex-gold Mining Soil Co...mentioning
confidence: 99%
“…Beberapa penelitian telah menemukan dampak negatif dari kegiatan penambangan emas yaitu aktifitas mikroba tanah menurun, kualitas tanah dan tanaman menurun, tanah bekas tambang bertekstur dominan pasir, kandungan bahan organic 1,036% (Sangat rendah), berat volume >1 g/cm 3 (Penyebab pemadatan tanah), struktur tanah rusak, aerasi dan drainase tanah serta retensi airnya rendah (Afandi, 2014;Henrianto et al, 2019). Salah satu logam berat berbahaya yang terkandung pada limbah tambang emas yaitu Merkuri (Hg).…”
Section: Pendahuluanunclassified